Prevalence of Gram Positive and Gram Negative Bacteria in Urinary Tract Infection - Salih, Aqeel M. (American Journal of Biology and Natural Sciences, 2025)
Objective: With the objective to identify both Gram-positive and Gram-negative species, the current study looks into the bacterial agents that cause urinary tract infections (UTIs). It also seeks to ascertain which age and gender groups among patients from Iraq’s Wasit Governorate are most vulnerable to infection. Methods: Between October 2023 and January 2024, 128 urine samples were taken from patients at Al-Karama General Hospital who ranged in age from 2 to 75. Following aerobic cultivation of the samples on Blood agar and MacConkey agar, isolates were identified by morphology, Gram staining, and biochemical profiling. Records were kept of the patient’s medical history and risk factors, including diabetes, catheter use, and prior antibiotic exposure. Results: Among the analyzed samples, 56% yielded bacterial growth. Staphylococcus spp. emerged as the predominant pathogen (41%), followed by E. coli (27%), Klebsiella spp. (12%), and Pseudomonas spp. (7%). Females exhibited a higher infection rate (69%) compared to males (59%). The 2–22 age group showed the highest infection prevalence (41.8%). Diabetes and prior antibiotic exposure were significantly linked to increased infection rates. Conclusions: The current study discovers a relationship between gram positive bacteria which are primarily responsible for urinary tract infections and less degree gram negative bacteria, with Escherichia coli accounting for the majority of these bacteria.